Into the eyes of the referee: A comparison of elite and sub-elite football referees` on-field visual search behaviour when making foul judgements - van Biemen, T.; Oudejans, R. R. D.; Savelsbergh, G. J. P.; Zwenk, F.; Mann, D. L. (International Journal of Sports Science & Coaching, 2023)
In foul decision-making by football referees, visual search is important for gathering task-specific information to determine whether a foul has occurred. Yet, little is known about the visual search behaviours underpinning excellent on-field decisions. The aim of this study was to examine the on-field visual search behaviour of elite and sub-elite football referees when calling a foul during a match. In doing so, we have also compared the accuracy and gaze behaviour for correct and incorrect calls. Elite and sub-elite referees (elite: N = 5, Mage ± SD = 29.8 ± 4.7yrs, Mexperience ± SD = 14.8 ± 3.7yrs; sub-elite: N = 9, Mage ± SD = 23.1 ± 1.6yrs, Mexperience ± SD = 8.4 ± 1.8yrs) officiated an actual football game while wearing a mobile eye-tracker, with on-field visual search behaviour compared between skill levels when calling a foul (Nelite = 66; Nsub-elite = 92). Results revealed that elite referees relied on a higher search rate (more fixations of shorter duration) compared to sub-elites, but with no differences in where they allocated their gaze, indicating that elites searched faster but did not necessarily direct gaze towards different locations. Correct decisions were associated with higher gaze entropy (i.e. less structure). In relying on more structured gaze patterns when making incorrect decisions, referees may fail to pick-up information specific to the foul situation. Referee development programmes might benefit by challenging the speed of information pickup but by avoiding pre-determined gaze patterns to improve the interpretation of fouls and increase the decision-making performance of referees.